Surface Sulfuration of NiO Boosts the Performance of Inverted Perovskite Solar Cells. Issue 10 (23rd July 2020) - Hu, Chen; Bai, Yang; Xiao, Shuang; Tao, Kewen; Ng, Wai Kit; Wong, Kam Sing; Cheung, Sin Hang; So, Shu Kong; Chen, Qi; Yang, Shihe
Abstract : As one of the most promising hole‐transporting materials for perovskite solar cells (PSC), NiO is widely used in the inverted p–i–n cell structure due to its high stability, decent hole conductivity, and easy processability for hysteresis‐free cells. However, the efficiency of NiO‐based PSCs is still low, due largely to the poor perovskite/NiO interface. Herein, a sulfur‐doping strategy to modify NiO surface via ion exchange reaction by a simple and scalable chemical bath deposition technique is introduced, which greatly improves the photovoltaic (PV) performance of the derived devices. A systematic investigation is shown where sulfur doping leads to favorable interfacial energetics with a reduced V oc loss. Sulfur doping at the interface also improves the contact between NiO and perovksite and facilitates the formation of high‐quality perovskite films. Carrier dynamics studies demonstrate reduced defect states and trap‐assisted recombination with sulfur doping, which promote the PV performance of the devices. These merits contribute concurrently to low‐loss charge transfer across the perovskite/NiO interface and facilitate charge transport through the perovskite films, leading to a high champion efficiency of 20.43% of the p–i–n structure solar cell devices. Abstract : A simple and effective sulfur‐doping method–based chemical bath deposition is introduced to improve interface contact between NiO and perovskite for efficient inverted perovskite solar cells. Sulfur doping leads to promoted perovskite film quality with reduced amount of grain boundaries and trap‐assisted charge recombination. The champion efficiency based on MAPbI3 reaches 20.43% in the NiO‐based inverted photovoltaic (PV) device.